2017
DOI: 10.14687/jhs.v14i4.5009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of in-service education on nurses’ preference for the ventrogluteal site in intramuscular injection implementation

Abstract: Purpose: This study conducted to determine the effect of in-service education on nurses' preference for the ventrogluteal site in intramuscular injection implementation. Method and materials: In this intervention study, the sample comprised 45 clinic nurses, where intramuscular injection practice is frequently applied. In-service education was conducted with regards to applying intramuscular injection to the ventrogluteal site. In the content of the planned education, the transmission of theoretical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In the present study, the nurses who learned injection into the VG site during nursing education had a higher total mean score of knowledge about VG compared to those who did not learn it. In the literature, there are studies indicating that the education provided to nurses about the use of the VG site in IM injection increases their level of knowledge (Arslan & Özden, 2018; Gülnar & Özveren, 2016; Öztürk et al, 2017). In the study of Öztürk et al (2017) in Turkey, 84.44% and 22.22% of the nurses preferred the DG site and the VG site, respectively, in primary nursing education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the nurses who learned injection into the VG site during nursing education had a higher total mean score of knowledge about VG compared to those who did not learn it. In the literature, there are studies indicating that the education provided to nurses about the use of the VG site in IM injection increases their level of knowledge (Arslan & Özden, 2018; Gülnar & Özveren, 2016; Öztürk et al, 2017). In the study of Öztürk et al (2017) in Turkey, 84.44% and 22.22% of the nurses preferred the DG site and the VG site, respectively, in primary nursing education.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies indicating that the education provided to nurses about the use of the VG site in IM injection increases their level of knowledge (Arslan & Özden, 2018; Gülnar & Özveren, 2016; Öztürk et al, 2017). In the study of Öztürk et al (2017) in Turkey, 84.44% and 22.22% of the nurses preferred the DG site and the VG site, respectively, in primary nursing education. After in‐service training, the number of administration of IM injection into the VG site increased among nurses, which might be an indicator of the effectiveness of the training given with the use of the VG site in IM injection practices.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that nurses still preferred DG region although there was an increase in the nurses' preferences on VG region is similar to the present study results (Table 3). It is also seen in other studies that nurses' knowledge levels about VG region and frequency of preferring this region increased with the training (Sarı et al 2017;Öztürk et al 2017). It was shown that the most important reason affecting the students' preference on VG region before and after the training was the fact that clinical nurses did not prefer VG region (Table 3).…”
Section: Discussionmentioning
confidence: 52%